'Set up to Fail'? How Welfare Conditionality Undermines Citizenship for Vulnerable Groups. Issue 2 (10th January 2017) - Reeves, Aaron; Loopstra, Rachel
Abstract : Underpinned by the assumption that unemployed persons are passive recipients of social security, recent welfare reforms have increased benefit conditionality in the UK and introduced harsher penalties for failure to meet these conditions. Yet, conditionality may result in vulnerable groups disproportionately experiencing disentitlement from benefits, one of the rights of social citizenship, because they are, in some cases, less able to meet these conditions. Rising sanctions, then, may be the product of a disconnection between welfare conditionality and the capabilities of vulnerable claimants. To test this hypothesis, we evaluate whether sanctions are higher in areas where there are more vulnerable Jobseeker's Allowance claimants, namely, lone parents, ethnic minorities and those with disabilities. We find that sanction rates are higher in local authorities where more claimants are lone parents or live with a disability, and that this relationship has strengthened since the welfare reforms were introduced under the Conservative-led coalition. Failure to meet conditions of benefit receipt may disproportionately affect vulnerable groups.